A new species of Hieracium sect. Pannosa (Asteraceae) from Bulgaria - Szeląg, Zbigniew; Vladimirov, Vladimir (Phytotaxa, 2013)
Hieracium crinitopannosum, a new species of presumably hybrid origin between H. petrovae and H. crinitum, is described from the Rhodopes in southern Bulgaria and illustrated. It is similar to H. cappadocicum from Turkey, but differs in the densely and conspicuously serrate-dentate leaves. The new species is triploid (x=9) and reproduces apomictically.